2023
DOI: 10.1001/jamapsychiatry.2023.2195
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Acute Care Use for Mental Health Conditions Among Youth During the COVID-19 Pandemic

Abstract: ImportanceUnderstanding how children’s utilization of acute mental health care changed during the COVID-19 pandemic is critical for directing resources.ObjectiveTo examine youth acute mental health care use (emergency department [ED], boarding, and subsequent inpatient care) during the second year of the COVID-19 pandemic.Design, Setting, and ParticipantsThis cross-sectional analysis of national, deidentified commercial health insurance claims of youth mental health ED and hospital care took place between Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…In addition, they found a 7% reduction in the percentage of youth with outpatient MH visits before their ED visit from the prepandemic period to the second pandemic year. 1 Further, they confirmed findings reported in other studies of pandemic year 1 that the percentage of youth with any MH ED visit decreased for that year relative to the period before. Given these findings, Overhage and colleagues 1 noted that other studies reported (1) relatively low rates of MH treatments provided while youth were in the ED, (2) parents expressing discomfort with ED experiences like long boarding periods, and (3) such ED experiences being a source of clinician burnout.…”
supporting
confidence: 87%
See 4 more Smart Citations
“…In addition, they found a 7% reduction in the percentage of youth with outpatient MH visits before their ED visit from the prepandemic period to the second pandemic year. 1 Further, they confirmed findings reported in other studies of pandemic year 1 that the percentage of youth with any MH ED visit decreased for that year relative to the period before. Given these findings, Overhage and colleagues 1 noted that other studies reported (1) relatively low rates of MH treatments provided while youth were in the ED, (2) parents expressing discomfort with ED experiences like long boarding periods, and (3) such ED experiences being a source of clinician burnout.…”
supporting
confidence: 87%
“…egory associated with increased visits, with increased suicidal ideation, particularly for female youth. 1 Overhage et al 1 found that youth from areas with a higher percentage of Asian, Black/African American, Hispanic, multiracial, and Native Hawaiian or Other Pacific Islander adolescents had a greater increase in ED MH visits than White adolescents. In addition, they found a 7% reduction in the percentage of youth with outpatient MH visits before their ED visit from the prepandemic period to the second pandemic year.…”
mentioning
confidence: 99%
See 3 more Smart Citations